Mahoni wood (Swietenia macrophylla King) contains holoseloluse and lignin. This research has been conducted to using lignin from mahoni wood for made polyurethane Isolate lignin is product isolation mahoni degradation with method increasing 4 gram isolate lignin into 150 ml ethylene glycol content 25 gram solution NaOH. The result of degradation used to synthesis polyurethane, then content of LT-PEG with methylen 4.4 difenil diisocyanaate (MDI) become polyurethane. To identified isolate ligni - Mohammad WIJAYA; I Made ARCANA (Departemen Hasil Hutan, IPB, 2009)
Mahoni wood (Swietenia macrophylla King) contains holoseloluse and lignin. This research has been conducted to using lignin from mahoni wood for made polyurethane Isolate lignin is product isolation mahoni degradation with method increasing 4 gram isolate lignin into 150 ml ethylene glycol content 25 gram solution NaOH. The result of degradation used to synthesis polyurethane, then content of LT-PEG with methylen 4.4 difenil diisocyanaate (MDI) become polyurethane. To identified isolate lignin and product degradation lignin has been conducted to characterized with UV and FTIR method. The result shows that the specified spectra at maximum wavelength at 280 nm and 248 nm. While result from FTIR spectra shows that spevtra at wavenumber 1296 cm-1 and 1249 cm-1 is shows of propile guaiasil group. The function group propel siringile. While lignin from kind at siirngile, while the spectra at 1354 cm-1. The result synthesis polyurethane to characterized by the mechanical properties analysis with Tensile tester machine. It is therefore mechanical properties shows that Tensile strength and Young modulus bigger wuth enhancing lignin of content into polyurethane but percentage elongation increase. Keywords : Mahoni wood, isolate lignin, degradation lignin, polyurethane